Portuguese airport efficiency analysis: The case study of Oporto - Dos-Santos, Maria José Palma Lampreia (2015)
The Oporto Airport located in the northern region in Porto city is crucial because is the only one located in the northern region. This airport had an increasing in number of passengers, sales revenue and accumulated investment during the last two decades, principally after the introduction and the operation of the Low Cost Companies since 2004 to the present. In order to determine if the last changes had an impact in the competitiveness of this airport, the main aims is to analise the evolution of values of the technical efficiency and equate the results before and after the introduction of the LCCs in this airport. The methodology uses the Data Envelopment Analysis. Results show that the Oporto Airport efficiency increases highly after the introduction of LCCs since 2004. The main conclusions suggest the importance of the introduction of LCCs in the increasing efficiency of the Oporto Airport and the potential relation with tourism development in this region, but more strong studies are needed.